2007
DOI: 10.1016/j.jacc.2007.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Pretreatment Improves Outcomes in Patients With Acute Coronary Syndromes Undergoing Early Percutaneous Coronary Intervention

Abstract: The ARMYDA-ACS trial indicates that even short-term pretreatment with atorvastatin may improve outcomes in patients with ACS undergoing early invasive strategy. These findings may support routine use of high-dose statins before intervention in patients with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
282
3
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(309 citation statements)
references
References 38 publications
9
282
3
15
Order By: Relevance
“…The efficacy of statins for preventing acute events in ACS patients was also demonstrated by the ARMYDA3 study. 20 In the recently published ARMYDA-RECAPTURE study, 21 patients with stable coronary artery disease were also enrolled, and inhibition of acute events after coronary intervention was demonstrated. Though the statin doses varied among these studies, inhibition of events was always found early, supporting the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of statins for preventing acute events in ACS patients was also demonstrated by the ARMYDA3 study. 20 In the recently published ARMYDA-RECAPTURE study, 21 patients with stable coronary artery disease were also enrolled, and inhibition of acute events after coronary intervention was demonstrated. Though the statin doses varied among these studies, inhibition of events was always found early, supporting the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accumulating clinical evidence points to the favorable effects of statins on restenosis following stent deployment (22)(23)(24). However, all clinical studies (25)(26)(27)(28), with a single exception (29), have reported a lack of significant effect for statins in preventing restenosis after PCI. Statins, similar to nitrogen-containing bisphosphonates (nBPs), are inhibitors of the mevalonate pathway blocking the prenylation of small GTPases, such as Ras, Rho, and Rac (22).…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании ARMYDA-ACS (Atorvastatin for Reduc tion of MYocardial Damage During Angioplasty-Acute Coronary Syndromes) назначение аторвастатина в дозе 80 мг за 12 часов до ЧКВ с добавлением 40 мг аторвастатина перед процедурой на фоне 600 мг нагрузочной дозы клопидогре-ла и 100 мг ацетилсалициловой кислоты больным ИМ без подъема сегмента ST с последующим их переходом на прием 40 мг аторвастатина в течение 30 дней сопровожда-лось снижением риска развития ИМ в 3 раза (р = 0,04) и всех ССО (смерть, ИМ, незапланированная реваскуляриза-ция миокарда) в 3,4 раза (р = 0,01) [20]. Выполненный в исследовании многофакторный анализ идентифицировал терапию аторвастатином перед инвазивным вмешатель-ством в качестве предиктора низкого риска ССО к 30-му дню (ОР 0,12, 95% доверительный интервал 0,05-0,50, p = 0,004) в отличие от терапии бета-блокаторами и инги-биторами ангиотензинпревращающего фермента.…”
Section: положение 7: гиполипидемическая терапия в отдельных группахunclassified